Vertical nontransovarial transmission of Bartonella in fleas. Issue 18 (23rd July 2013) - Morick, Danny; Krasnov, Boris R.; Khokhlova, Irina S.; Gutiérrez, Ricardo; Gottlieb, Yuval; Harrus, Shimon
Abstract: Pathogens use diverse pathways to infect host populations by vertical and/or horizontal routes. Horizontal transmission of bacteria belonging to the Bartonella genus via haematophagous vectors is well known. Vertical transmission of Bartonella species was also suggested to occur but its routes remain to be unveiled. In a previous study, we showed the absence of transovarial transmission of Bartonella species OE 1‐1 in Xenopsylla ramesis fleas, and that fleas feeding on Bartonella ‐positive jirds produced Bartonella ‐positive gut voids. This current study aimed to investigate whether vertical nontransovarial transmission of Bartonella occurs in fleas. For this aim, the X. ramesis–Bartonella sp. OE 1‐1 model was used. Four groups of fleas including Bartonella ‐positive and Bartonella ‐negative female fleas and larval offspring had access to either Bartonella ‐negative or Bartonella ‐positive gut voids and faeces. Sixteen per cent of flea offspring that had access to Bartonella ‐positive faeces and gut voids became Bartonella positive. Our findings demonstrate that Bartonella ‐positive flea faeces and gut voids are proper infection sources for flea larvae and indicate that vertical nontransovarial transmission of bartonellae occurs in fleas. This information broadens our understanding of Bartonella transmission routes in flea vectors and enlightens pathways of bartonellae transmission and maintenance in flea populations in nature.